2018
DOI: 10.1177/0363546518760580
|View full text |Cite
|
Sign up to set email alerts
|

Greater Static Anterior Tibial Subluxation of the Lateral Compartment After an Acute Anterior Cruciate Ligament Injury Is Associated With an Increased Posterior Tibial Slope

Abstract: An increased PTS was identified to be an independent anatomic risk factor of increased (≥6 mm) anterior subluxation of the lateral compartment in acute noncontact ACL injuries. For patients with obviously increased anterior tibial subluxation of the lateral compartment after ACL injuries, the PTS should be measured.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 23 publications
4
49
0
Order By: Relevance
“…The most evident result is that the PTS was larger in the study group than that in the control group. This was similar to the recent epidemiological study performed by Song et al, 25 in which increased PTS was identified as an independent anatomic risk factor of excessive (>10 mm) ATS in extension after ACL injury. In that study, the mean PTS of the patients with excessive (>10 mm) ATS in extension was 16.6°, suggesting that a larger PTS may lead to an anteriorly subluxated tibial position after ACL injury.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The most evident result is that the PTS was larger in the study group than that in the control group. This was similar to the recent epidemiological study performed by Song et al, 25 in which increased PTS was identified as an independent anatomic risk factor of excessive (>10 mm) ATS in extension after ACL injury. In that study, the mean PTS of the patients with excessive (>10 mm) ATS in extension was 16.6°, suggesting that a larger PTS may lead to an anteriorly subluxated tibial position after ACL injury.…”
Section: Discussionsupporting
confidence: 92%
“…24,27 Increases in ATS in extension have been observed in the setting of combined posterior horn of medial and lateral meniscal tears. 7,18 Furthermore, increased posterior tibial slope (PTS) has been shown to portend greater ATS in extension in ACL-deficient knees; Song et al 25 found that patients who had excessive (>10 mm) ATS in extension (resting pivot-shift position) after ACL injury all had PTS >15°. Alterations of the PTS may result in an anterior shift of the resting position of the tibia relative to the femur.…”
mentioning
confidence: 99%
“…First, the value of ATSLC obtained in the supine position may not represent what truly occurs in the weightbearing situation. However, nearly all previous studies investigating the ATSLC in extension performed the measurements on nonweightbearing MRI or fluoroscopy, 2-4,17,26,28,29,36,37 which makes our results comparable with previous literature. Second, a meniscal lesion with a length ≤10 mm between its location and LMPR tibial attachment as measured by the intra-articular probe was determined to be a radial tear by a single researcher, which probably brought subjectivity to the classification of LMPR lesions.…”
Section: Discussionsupporting
confidence: 84%
“…Steep PTS was recently identified as an independent anatomic risk factor of excessive static ATS in extension (>10 mm) after ACL injury. 28 In that study, the mean PTS of the patients with excessive ATS in extension (>10 mm) was 16.6°. Grassi et al 13 suggested that the steep PTS combined with excessive ATS in extension (>10 mm) after ACL injury represented the “worst-case scenario” for ACLR.…”
Section: Discussionmentioning
confidence: 76%